Use and exchange of genetic resources of Nile tilapia ( Oreochromis niloticus ) - Ambekar E. Eknath; Gideon Hulata (Reviews in Aquaculture, 2009)
The worldwide use of Nile tilapia ( Oreochromis niloticus Linnaeus, 1758) in aquaculture represents a somewhat unique scenario. The natural distributions and global genetic resources of tilapias are in Africa, yet the main centers of utilization for aquaculture are primarily in Asia. Within a few decades, Nile tilapia graduated from being an ‘orphan commodity’ (i.e. of interest to only resource‐poor fish farmers) to a globally traded commodity. Most aquaculture production of Nile tilapia in Asia and elsewhere has relied on a narrow genetic base. The natural genetic resources have not yet been fully documented and tapped for use in aquaculture, and many natural populations are under severe threat of irreversible change or loss. Although genetic improvement is now well underway, an important question is how the wealth of Nile tilapia wild genetic resources shall be used for the benefit of a wide range of users, at present outside Africa. This review focuses on documenting the status of Nile tilapia genetic resources (including the potential threats), providing a case for their conservation and for the judicious utilization of genetic diversity for the benefit of all stakeholders; and on analysis of the lessons learnt from a major Nile tilapia genetic improvement initiative, the genetic improvement of farmed tilapia (GIFT) project. Information about other genetic improvement efforts by means of hybridization, sex reversal and YY male technology is also presented.